Implementasi Kurikulum Tersembunyi Pada Mata Pelajaran Pendidikan Agama Islam di SMA Negeri 1 Rejang Lebong - Warsah, Idi; Destriani; Yudhi Septian, Rahmat; Nurhayani (Program Studi Pendidikan Agama Islam, 2022)
The discourse on the hidden curriculum has not yet been scientifically touched upon in studies oriented towards curriculum in the Indonesian context. Therefore, this qualitative research seeks to address the discourse on the hidden curriculum. This study aimed to investigate the implementation of the hidden curriculum in the Islamic religious education subject at SMA Negeri 1 Rejang Lebong. Informants in the study were the Principal of SMAN 1 Rejang Lebong and Islamic Education Teachers. The data were garnered using in-depth interviews with the informants. The data were then analyzed using an interactive model. This study found that SMA Negeri 1 Rejang Lebong had implemented the hidden curriculum effectively. The implementation of the hidden curriculum included the integration of local culture with marriage-teaching materials and the use of references to the Kitab Kuning published by Middle Eastern countries as additions and reinforcements. The hidden curriculum was also implemented by inculcating the insight of religious moderation and Islamic understanding of Wasathiyah as a counter to the takfiri and intolerant thoughts that were circulated and widespread in cyberspace. This was done to fortify students' religious understanding so that it did not lead to a radical or liberal understanding.